COMPONENTS OF AGGRESSIVENESS IN GIBBERELLA FUJIKUROI POPULATIONS FROM SOUTH ROMANIA - Ittu, Mariana; Ciocazanu, Ion (Plant Breeding and Seed Science, 2011)
For breeding purposes, use of reliable Fusarium isolates and inoculation techniques for assessment of host resistance are key components for developing strategies to mitigate the risks caused by this pathogen in maize. Results of evaluating aggressiveness of Fusarium accessions obtained in 2008 from five locations from South Romania, under both seedling and field artificial inoculation in 2009, in terms of coleoptile length (% of control), visual score (1-9) and fumonisin content (FUM, ppm), are reported. High aggressive potential was found in all populations regardless of their geographic origin. Mean percentage values of coleoptile length across three maize hybrids inoculated with 30 Fusarium verticillioides isolates collected in 2008 (six/per location) and two types of culture media, ranged in seedling stage from 15.8 (Braila) to 19.7 (Valul lui Traian). A large variability in accumulation of FUM in grains corresponding to 26 maize genotype x Fusarium isolate combinations averaged over two culture media, was found in 2009 inoculated experiment. A significant close negative correlation between visual score andFUM content was found when 61 maize genotypes have been inoculated with FUN 640-1-2/2006 isolate in 2008.